Human T cell leukaemia/lymphoma virus infection in pregnant women in the United Kingdom: population study. Issue 7248 (3rd June 2000) - Ades, A E; Parker, Simon; Walker, Jane; Edginton, Mark; Taylor, Graham P; Weber, Jonathan N
Abstract: Objective: To assess the prevalence of human T cell leukaemia/lymphoma virus (HTLV) infection in pregnant women in the United Kingdom. Design: Population study. Subjects: Guthrie card samples from babies born in 1997-8.Samples were linked to data on mother's age and ethnic status and parents' country of birth and then anonymised. Setting: North Thames Regional Health Authority. Main outcome measures: Presence of antibodies against HTLV in eluates tested by gelatin particle agglutination assay and results confirmed by immunoblot. Results: Of 126 010 samples tested, 67 had confirmed antibodies to HTLV (59 HTLV-I, 2 HTLV-II, 6 untyped) and six had indeterminate results. Seroprevalence was 17.0 per 1000 (95% confidence interval 9.2 to 28.3) in infants whose mothers were born in the Caribbean, 3.2/1000 (1.5 to 5.9) with mothers born in west and central Africa, and 6.8/1000 (3.1 to 12.9) in infants of black Caribbean mothers born in non-endemic regions. In infants with no known risk (both parents born in non-endemic regions and mother not black Caribbean) seroprevalence was 0.06-0.12 per 1000. Mother's country of birth, father's country of birth, and mother's ethnic status were all independently associated with neonatal seroprevalence. An estimated 223 (95% confidence interval 110 to 350) of the 720 000 pregnant women each year in the United Kingdom are infected with HTLV. Conclusions: The prevalence of HTLV and HIV infections in pregnant women in the United Kingdom are comparable. The cost effectiveness of antenatal HTLV screening should be evaluated, and screening of blood donations should be considered.